Determinants of the relative effectiveness of fiscal policy in the Iraqi economy for the period (1989-2017) - Salam Kazem Shani Al – Fatlawi (Iraqi Journal for Administrative Sciences, 2024)
The study examined the measurement and analysis of the relative effectiveness of fiscal policy tools (taxes and expenditures) in the Iraqi economy for the period 1989-2017. The government can stabilize the economy by using fiscal policy tools to influence the level of real GDP, depending on the level of the country's economic development and output structure. The research started from the premise that fiscal policy plays a major role in achieving economic stability, relying on the structure of the country's GDP, so activating the role and contribution of the private sector in the output will enhance the effectiveness of fiscal policy instruments. The importance of research is to clarify the relative effectiveness of fiscal policy in the Iraqi economy for the period 1989-2017. The research was based on the inductive method of economic analysis to follow the evolution of economic variables for research through a time series, and then extrapolating the economic reality and analysis of economic phenomena and development during the research period, and then derive the economic effects resulting from them. To illustrate the effectiveness of fiscal policy instruments in GDP, economic measurement was used through the use of ARDL. One of the main conclusions of the research is that current expenditures have no significant short- and long-term impact on GDP, nor do taxes and investment expenditures have a long-term effect on GDP. This means that fiscal policy is ineffective in Iraq's economy Short and long.